Supplier Selection and Service Quality in Public Entities: A Case Study Kabale District Local Government. - Mukamayebare, Rogers (Kabale University, 2023)
The main purpose of the study was to examine the impact of Supplier selection and service quality in public entities. A case study of Kabale District Local Government. The researcher used qualitative research design to gather data from across sections of the same size population. The study population comprised 28 employees of the district, 18 suppliers 12 members of the public, and other stakeholders totaling 58 respondents. On determinants of Supplier selection and service quality among PDUs Kabale district local Government, the findings revealed that the majority of respondents strongly agree with prices, quality, communication system, and performance history. The study findings further revealed that the majority of respondents strongly agree with recognizing the need for supplier selection, determining the method of Supplier evaluation and selecting the supplier and reaching the agreement, identifying the key sourcing requirements, determining the sourcing strategy, identifying the potential supply sources and reducing the suppliers' number in the selection pool. The study findings revealed that most of the respondents strongly agree with cost criteria, technical capability, quality assessment, service levels and ease of communication, price, and risk factors affecting supplier selection and service quality among PDUs Kabale district local Government. Also, 10(17) and 2(3) percent of the respondents strongly agree with distribution cost and supplier's profile respectively.